Z-scan measurements and TDDFT study of the two-photon absorption properties of diaqua-bis(4-hydroxy-3-methoxybenzaldehyde)-cobalt(II). (11th December 2016) - Li, Tingbin; Hu, Yali; Ma, Chunlin; Wang, Shenglai; Xu, Dong
ABSTRACT: A cobalt complex constructed by the ligand(L): 4-hydroxy-3-methoxybenzaldehyde [Co(C8 H7 O3 )2 (H2 O)2 ] has been synthesized and characterized by X-ray single crystal diffraction. The cobalt(II) atom is six-coordinate in a distorted octahedral geometry, intermolecular O-HO hydrogen bonds lead to the formation of a two-dimensional supramolecular network along ab plane. Its thermal stability was determined by TGA/DSC. Its two-photon absorption (TPA) cross-section σ2 value and second hyperpolarizability γ value were determined to be 1.59 × 10 −53 (m 4 · s/photon · molecule) and 1.06 × 10 −56 (C · m 4 /V 3 ) by Z-scan technique with 20 picosecond (ps) pulses at wavelength 1064 nm. The γ value is about six times larger than the time-dependent density-functional theory (TDDFT) calculation results.